Crab Mentality from the Perspective of the Prophet's Hadith: Implications for Social Ethics in Islamic Education - Dinar Mahesa Putri (eL-HIKMAH: Jurnal Kajian dan Penelitian Pendidikan Islam, 2026)
The phenomenon of crab mentality is a form of social behavior characterized by the tendency to hinder and undermine the success of others, which often appears in various social relationship contexts, including in educational environments. In educational practice, such attitudes have the potential to weaken the value of togetherness, damage the academic climate, and hinder the character-building process of students. This article aims to analyze the phenomenon of crab mentality from the perspective of the Prophet's hadith and examine its implications for social ethics in Islamic education. This research uses a qualitative approach thru library study with the thematic hadith method (maudhu'i). The primary data sources come from hadiths relevant to the themes of social relations, envy, and brotherhood in Sunan At-Tirmidhi and Sunan Abu Dawud, while the secondary sources include hadith commentary books and related scientific literature. The analysis results show that the Prophet's hadiths explicitly criticize envy, hatred, and actions that disrupt social harmony, which are substantially in line with the characteristics of crab mentality. These findings affirm that the social ethical values in hadith are of significant relevance to Islamic education, particularly in fostering a healthy academic culture, fair competition, and educational relationships based on empathy and mutual respect.